(untitled) (Journal of Applied Oral Science, 2010)
OBJECTIVE: The aim of this retrospective analysis was to determine the age, gender, frequency and distribution of trauma-associated hard tissue and soft tissue lesions of the oral and maxillofacial region in a population from southern Taiwan. PATIENTS AND METHODS: Approximately 10% of the 27,995 biopsy records of patients with history of trauma resulting in lesions who were treated at our institution between 1991 and 2006 were examined for this study. RESULTS: In the included records, there were 2,762 soft tissue and 26 hard tissue lesions. Mucocele was the most frequent trauma-associated soft tissue lesion (955 cases). The youngest patients were those who presented with mucocele (mean age = 27.3 years), while the oldest patients were those with peripheral giant cell granuloma (58 years). The lower lip was the most frequent site of occurrence of mucocele (676, 64.5%) and was also the predominant site of occurrence of all soft tissue lesions (815, 29.5%), followed by the buccal mucosa (654, 23.4%) and the tongue (392, 14.2%). Trauma-associated hard tissue lesions included only osteoradionecrosis (24 cases) and traumatic bone cysts (2 cases). CONCLUSION: As little data of this nature have been reported from populations of Asian developing countries, the findings of this retrospective analysis is valuable for epidemiological documentation of type of traumatic oral lesions as well as for informing the professionals and the layman about the importance of this category of oral lesions.